Malaysian in-service teachers’ intrinsic and extrinsic motivation towards teaching English - Ismail, Shajna (IIUM Press, 2023)
The most extensively studied second language in the world, English is the language of the global economy. It is crucial to understand whether instructors are sufficiently motivated at different stages of their professional journeys because good teaching isa prerequisite for students' learning. This study aimed at investigating the overall motivation of in-service English language teachers in Malaysia. Employing a quantitative research design, a survey instrument was used to collect data from in-service English teachers who are currently doing their undergraduate degree. They were requested to respond to the items on motivation, which are categorized into two sub-dimensions, intrinsic and extrinsic. The study reveals that Malaysian in-service English teachers are generally motivated to teach English, whereas the motivation comes mostly from the intrinsic aspects. The findings have significant implications on the Malaysian educational policy and system as well as its various professional development programs for teachers generally, and English teachers specifically.